Effect of sawtooth crashes on fast ion distribution in NSTX-U. (3rd July 2018) - Liu, D.; Heidbrink, W.W.; Podestà, M.; Hao, G.Z.; Darrow, D.S.; Fredrickson, E.D.; Kim, D.
Abstract: During the 2016 experimental campaign of NSTX-U (Menard et al 2012 Nucl. Fusion 52 083015), long L-mode and reproducible sawtoothing plasmas have been achieved that were previously not accessible before the upgrade. This provides a good opportunity to study the effect of sawtooth crashes on fast ion confinement and redistribution in spherical tokamaks. The solid-state neutral particle analyzer (SSNPA) and fast ion D-alpha (FIDA) diagnostics on NSTX-U each have a tangentially-viewing instrument and a radially- or vertically-viewing instrument, which are mainly sensitive to passing and trapped fast ions, respectively. It has been observed on both diagnostics that passing particles are strongly expelled from the plasma core to the edge during sawtooth crashes, while trapped fast ions are weakly affected. The tangentially-viewing SSNPA observes large signal spikes at the sawtooth crashes because fast ions move to the edge and charge exchange with edge neutrals. The radially-viewing SSNPA data suggest that there is a small drop of trapped particles in the core. The tangentially-viewing FIDA (t-FIDA) system observes a depletion as large as 25% in the region inside the inversion radius, while an increase at the outer region. There is almost no change in the signals of the vertically-viewing FIDA system. The neutron emission can drop as much as 15% at the sawtooth crashes, accompanied by an increase of edge light. Simulations with the Kadomstev and Porcelli sawtooth models have been performed and compared with the measurements. The full reconnection Kadomtsev model overestimates the neutron rate drop at each sawtooth crash. When tuning the sawtooth input parameters, the partial reconnection Porcelli sawtooth model can qualitatively reproduce the neutron rate drop and t-FIDA signal drop in the core, but it fails to predict the t-FIDA signal increase at the edge.